Malignant cylindroma of the scalp treated with staged perimeter excision: A case report and literature review. (September 2019) - Kim, Stephanie M.; Truong, Jessica L.; Wu, Kitty; Gabril, Manal Y.; Grant, Aaron
Summary: Malignant cylindroma is a rare and poorly understood cutaneous malignancy. There is a paucity of literature on these lesions, with only a select number of case reports and limited guidelines on management. We present a case of a 60-year old patient with a malignant cylindroma of the scalp treated surgically with staged perimeter excision and summarize our review of the literature with a focus on management of this potentially aggressive disease.